Ataxia rating scales are age‐dependent in healthy children. (7th January 2014) - Brandsma, Rick; Spits, Anne H; Kuiper, Marieke J; Lunsing, Roelinka J; Burger, Huibert; Kremer, Hubertus P; Sival, Deborah A; Barisic, N.; Baxter, P.; Brankovic‐Sreckovic, V.; Calabrò, G.E.; et al.
<x xml:space="preserve">Abstract</x> Aim To investigate ataxia rating scales in children for reliability and the effect of age and sex. Method Three independent neuropaediatric observers cross‐sectionally scored a set of paediatric ataxia rating scales in a group of 52 healthy children (26 males, 26 females) aged 4 to 16 years (mean age 10y 5mo SD 3y 11mo). The investigated scales involved the commonly applied International Cooperative Ataxia Rating Scale (ICARS), the Scale for Assessment and Rating of Ataxia (SARA), the Brief Ataxia Rating Scale (BARS), and PEG‐board tests. We investigated the interrelatedness between individual ataxia scales, the influence of age and sex, inter‐ and intra‐observer agreement, and test–retest reliability. Results Spearman's rank correlations revealed strong correlations between ICARS, SARA BARS, and PEG‐board test (all p<0.001). ICARS, SARA, BARS and PEG‐board test outcomes were age‐dependent until 12.5, 10, 11, and 11.5 years of age respectively. Intraclass correlation coefficients (ICCs) varied between moderate and almost perfect (interobserver agreement: 0.85, 0.72, and 0.69; intraobserver agreement: 0.92, 0.94, and 0.70; and test–retest reliability: 0.95, 0.50, and 0.71; for ICARS, SARA, and BARS respectively). Interobserver variability decreased after the sixth year of life. Interpretation In healthy children, ataxia rating scales are reliable, but should include age‐dependent interpretation in children up to 12 years of age. To enable longitudinal interpretation of quantitative ataxia rating scales in children, European paediatric normative values are necessary.